2000
DOI: 10.1152/jappl.2000.89.4.1317
|View full text |Cite
|
Sign up to set email alerts
|

Venoarterial CO2 difference during regional ischemic or hypoxic hypoxia

Abstract: To test the role of blood flow in tissue hypoxia-related increased veno-arterial PCO(2) difference (DeltaPCO(2)), we decreased O(2) delivery (&Ddot;O(2)) by either decreasing flow [ischemic hypoxia (IH)] or arterial PO(2) [hypoxic hypoxia (HH)] in an in situ, vascularly isolated, innervated dog hindlimb perfused with a pump-membrane oxygenator system. Twelve anesthetized and ventilated dogs were studied, with systemic hemodynamics maintained within normal range. In the IH group (n = 6), hindlimb DO(2) was prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
141
0
17

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(172 citation statements)
references
References 12 publications
14
141
0
17
Order By: Relevance
“…Parte 2. Acta Cir Bras [serial online] 2002 Set-Out;17 (5). Disponível em URL: http://www.scielo.br/acb RESUMO -Evidências clínicas e experimentais substanciais indicam que o território circulatório mesentérico, principalmente na mucosa intestinal, é altamente vulnerável a redução na oferta de oxigênio e predisposto a lesão precoce na presença de alterações hemodinâmicas induzidas pela sepse e choque séptico.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Parte 2. Acta Cir Bras [serial online] 2002 Set-Out;17 (5). Disponível em URL: http://www.scielo.br/acb RESUMO -Evidências clínicas e experimentais substanciais indicam que o território circulatório mesentérico, principalmente na mucosa intestinal, é altamente vulnerável a redução na oferta de oxigênio e predisposto a lesão precoce na presença de alterações hemodinâmicas induzidas pela sepse e choque séptico.…”
Section: Discussionunclassified
“…Vallet et al 5 demonstrated, in a canine model of resuscitated endotoxic shock, a marked redistribution of blood flow within the gut wall, from the mucosa toward the muscularis, with a simultaneous decrease in intestinal mucosal PO 2 . These data contrast with Revelly et al, 6 who used microspheres to evaluate blood flow distribution within the intestinal wall during endotoxic shock in pigs.…”
Section: Splanchnic Blood Flow Distributionmentioning
confidence: 98%
See 1 more Smart Citation
“…In oxygen debt caused anaerobic metabolism, hydrogen ions are generated through the hydrolysis of ATP to ADP and increased production of lactic acid [43]. These hydrogen ions are buffered by bicarbonate presented in the cells, and this process will generate CO 2 production [44]. The Fick principle adapted to carbon dioxide demonstrates the inverse relationship between the CO and dCO 2 [45], in other words increased levels of dCO 2 reflect low flow states.…”
Section: Parameters Reflecting Vomentioning
confidence: 99%
“…Experimental studies on isolated limb [8] or small intestine mucosa [9], and further confirmed by theoretical mathematical models of CO 2 exchange during hypoxia [10] show that venous pCO 2 evolutions are different during ischemic and hypoxic hypoxia. The authors observed venous pCO 2 kinetics when reducing oxygen delivery beyond the critical threshold value while oxygen consumption becomes dependent on oxygen delivery.…”
mentioning
confidence: 94%